Renewable and Non-renewable Energy Consumption in Indonesia: Does it Matter for Economic Growth? - Aswadi, Khairul; Jamal, Abd.; Syahnur, Sofyan; Nasir, Muhammad (International Journal of Energy Economics and Policy, 2023)
During the last decade, the energy sector has become important in shaping a country's economy. This study aims to analyze renewable and non-renewable energy's impact on Indonesia's economic growth. This study uses a quantitative method, using the Johansen cointegration test and FMOLS and DOLS cointegrating regression. The data period used in this study is from 1980-2019. The results of the study show that renewable energy consumption has a negative effect on Indonesia's economic growth. This is because renewable energy production is still limited, but the level of consumption continues to increase. Consumption of non-renewable energy has a positive effect on Indonesia's economic growth. The consumption of fossil energy causes this is still very high in Indonesia. Dependence on fossil energy is still high amid renewable energy production, which the government is continuously promoting. In general, energy consumption positively affects Indonesia's economic growth. When the two are combined, they positively contribute to the national economy.